Etnografi Komunikasi Keluarga Berkasus Seks Bebas di Kota Padang - Havifi, Ilham; Sari, Lusi Puspika (Prodi Pendidikan Sejarah Fakultas Keguruan dan Ilmu Pendidikan Universitas Islam Sumatera, 2024)
This study addresses a fundamental issue in contemporary society: family communication. Specifically, it examines how parental communication patterns affect adolescents engaging in premarital sex, categorized as social welfare problem cases (PMKS) by the Social Services in three families in Padang City, specifically in the Olo Subdistrict of Padang Barat. Employing a qualitative research approach within a constructivist paradigm and employing ethnographic communication study methods, data on family communication dynamics and parental upbringing of adolescents involved in premarital sex in the Olo Subdistrict were gathered through observation and in-depth interviews. Purposive sampling was utilized to select informants. Findings reveal that parental communication with adolescents occurs through primary, secondary, and linear communication patterns, with obstacles such as semantic disturbances, conflicting interests, hidden motivations, and biases. Effective intra-family communication, characterized by openness, empathy, positive behavior, supportive attitudes, and equality, is essential for preventing social deviances like premarital sex and addressing other societal issues.